1981
DOI: 10.1113/jphysiol.1981.sp013700
|View full text |Cite
|
Sign up to set email alerts
|

Responses of pontine units to skin‐temperature changes in the guinea‐pig

Abstract: SUMMARY1. The responses of fifty-five single units to changes in skin temperature were recorded in twenty-three guinea-pigs anaesthetized with urethane. Skin-temperature changes were induced by changing the temperature of the water-perfused support plate of the stereotaxic apparatus and that of the double-walled Perspex jacket that was put on the support plate.2. Thirty-three units were stereotaxically and histologically verified as being within a circumscribed area of the pontine dorsomedial reticular formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 14 publications
3
6
0
Order By: Relevance
“…One group of cells referred to as the ‘pontine thermoregulatory area’ has been reported to respond to skin-temperature changes in the guinea pig [47, 48, 49]. It was suggested that the responding cells might be identical to subcoeruleus catecholaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…One group of cells referred to as the ‘pontine thermoregulatory area’ has been reported to respond to skin-temperature changes in the guinea pig [47, 48, 49]. It was suggested that the responding cells might be identical to subcoeruleus catecholaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Discrete lesions of the anterior hypothalamus can lead to either hyperthermia or hypothermia, whereas lesions in the posterior hypothalamic nucleus tend to produce hypothermia. Hypothermia may also occur when there is damage to the reflex thermoregulatory pathways traversing the brainstem or spinal cord [5][6][7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Neurones in the nucleus raphe magnus (NRM), a circumscribed area in the lower brain-stem, have been shown to belong to the thermoafferent system (Dickenson, 1977;Hinckel & Schroder-Rosenstock, 1981;Hinckel et al 1991). The response of 58 single units in the nucleus raphe magnus (NRM) to changes in abdominal, thoracic and leg skin temperature was recorded in 30 anaesthetized guinea-pigs (1.41 g urethane per kg body weight I.P.).…”
Section: Umds (St Thomas's) M1eetlygmentioning
confidence: 99%